Measurement of the t-channel single top quark production cross section - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, I.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; et al. (Elsevier B.V., 2010)
The do Collaboration reports direct evidence for electroweak production of single top quarks through the t-channel exchange of a virtual W boson. This is the first analysis to isolate an individual single top quark production channel. We select events containing an isolated electron or muon, missing transverse energy, and two, three or four jets from 2.3 fb(-1) of p (p) over bar collisions at the Fermilab Tevatron Collider. One or two of the jets are identified as containing a b hadron. We combine three multivariate techniques optimized for the t-channel process to measure the t- and s-channel cross sections simultaneously. We measure cross sections of 3.14(-0.80)(+0.94) pb for the t-channel and 1.05 +/- 0.81 pb for the s-channel. The measured t-channel result is found to have a significance of 4.8 standard deviations and is consistent with the standard model prediction. (C) 2009 Elsevier B.V. All rights reserved.